Morphological awareness and vocabulary: the examination of their relationship in kindergarten - Grigorakis, Ioannis (Psychology: the Journal of the Hellenic Psychological Society, 2022)
The aim of this study was to examine the relationship between morphological awareness and vocabulary. Participants were two hundred and fifteen Greek children tested in kindergarten. We evaluated three morphological awareness skills (inflection, derivation, and lexical compounding), receptive vocabulary and expressive vocabulary, along with other cognitive and language skills. The results of hierarchical regression analyses showed that each one of the three aspects of morphological awareness (inflectional, derivational, and compounding) predicted uniquely both receptive and expressive vocabulary. In addition, the results of hierarchical regression analyses showed that each one of the two types of vocabulary predicted uniquely each one of the three aspects of morphological awareness. These results add to our understanding of the relationship between these two developing skills as they suggested a reciprocal relationship. Moreover, the results underscore the potential importance of all aspects of morphological awareness in this relationship.